Working Paper on Population Growth and Natural Resource Pressures in Pursat Catchment - Ministry of Water Resources and Meteorology, Cambodia; Tonle Sap Authority; Supreme National Economic Council, Cambodia; Hatfield Consultants; Culture and Environment Preservation Association (CGIAR Challenge Program on Water and Food, 2013)
This project examined the linkages between population and demand for food and water. Cambodia, in general, and Pursat Province in particular, have a complex and interesting mosaic of demographic attributes and development issues. The Tonle Sap basin and Pursat catchment possess the country’s largest potential water resources. These resources have the ability to support on-going economic development, including irrigation and agricultural production, fisheries and aquaculture, energy and forest products, navigation and other modes of transport, domestic and industrial water use and tourism.